ANALISIS PRINSIP AL-ADALAH DALAM PUTUSAN PTUN NOMOR 604/G/2023/PTUN.JKT - Nuriyanti Nuriyanti; Mumtazinur Mumtazinur; Nurul Fitria (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The decision of the Jakarta State Administrative Court (PTUN) in Case Number 604/G/2023/PTUN.JKT, which annulled the Presidential Decree reappointing Anwar Usman as Chief Justice of the Constitutional Court, has sparked public debate regarding ethical governance and the principle of justice in state administration. This study aims to analyze the concept of justice (al-ʿadālah) from the perspective of siyāsah dustūriyyah and how it is reflected in the court's legal considerations. Using a normative juridical method with a qualitative approach, this research examines the alignment between Islamic constitutional theory and the values upheld in the PTUN ruling. The findings reveal that the judges emphasized impartiality, moral integrity, and the protection of public trust in state institutions—principles that resonate with the Islamic vision of justice, where leaders must be free from conflicts of interest and accountable for public duties. The study concludes that the PTUN decision embodies aspects of administrative justice that are in harmony with Al-Adalah ethics, and it highlights the critical role of legal oversight in preventing abuse of executive power in high-level appointments.